Google apps getting the most out of Google apps for business - Milton, Michael (CreativeLIVE in partnership with O'Reilly, 2010)
"Learn how to use Google Apps to collaborate, share information, build a community, and power your business. In this five-session video course 5-week course, you'll gain valuable knowledge and experience with these versatile web-based tools, including Google Docs (word processor, spreadsheet, presentation program, and drawing application), Google Calendar, Gmail, Google Sites for website creation, Google Video, Apps Marketplace, and more"--Resource description page (viewed Jan. 19, 2011).
Keywords: Google; Web search engines; Application software; Moteurs de recherche sur Internet; Logiciels d'application